Parents' beliefs, play organization, and children's preferenes, exploring outdoor play of preschool children - Salvaña, Kathrine Joy A.
This study was conducted to explore parents’ beliefs and children's outdoor play post-COVID-19 pandemic. It aims to explore parents' beliefs about outdoor play, how they organize it, and its connection to children's play frequency, and children's preferences for outdoor play environments. A descriptive correlational approach was used, which included both qualitative and quantitative features in the design, data collection, and analysis. The sample includes parents or primary caregivers of children studying in selected preschools in Quezon City, Philippines. Data were obtained from survey questionnaires from 94 parents or primary caregivers and photo-elicitation interviews with 10 children. Results showed that parents have high levels of play support and believe that outdoor play is important for their child’s development; however, the study results only found weak correlations between play support and frequency of outdoor play. The most frequent outdoor play activities for children are walking, running, and playing chase, while the most frequent outdoor environments where children spend time are playgrounds, gardens, garages, and streets. It was also found that children prefer to play on playgrounds, beaches, and swimming pools. In contrast, the least preferred outdoor environments are forests and parking spaces. Parents organize outdoor play by playing with their children, taking them to a location of play, optimizing the setting, utilizing available materials, and scheduling play activities. Although parents provide play opportunities and recognize the importance of outdoor play, they still believe that the amount of outdoor play their children get is insufficient. Results highlight the importance of optimizing outdoor play environments not just for children but also for the parents and their families to further foster outdoor play for young children.